Hundred years of research in garden history : Scientific conference headquarters of the Hungarian of sciences, 23 November 2012. - Jámbor , Imre (4D Journal of Landscape Architecture and Garden Art, 2013)
It seems unbelievable, but it's true that methodic research in garden art and history and reconstruction works based on it, as well as protective measures with the purpose of conservation reach back over hundred years in Hungary. This, at the same time also means that Hungarian garden history research always kept track of European development and belonged to its forefront for a long time. The same applies today, although Hungarian cultural heritage in garden art - thanks to centuries in history that shattered all the preceding ones - is very modest and small compared to the Western-European preserved, existing and protected heritage, but it still carries values that hallmark the performance of Hungarian garden art within European cultural history, despite all destruction.
Keywords: research in garden; hundred years